PRINCIPLES OF CREATION AND FUNCTIONING OF THE UNIFIED GEOINFORMATION ENVIRONMENT OF THE ARMED FORCES OF UKRAINE - Литвиненко , Н.І.; Коренець , О.В.; Федченко , О.П. (Військовий інститут Київського національного університету імені Тараса Шевченка, 2022)
In the course of research to ensure the general requirements for geographic information support of the Unified automated control system of the Armed Forces of Ukraine (UACS of the Armed Forces of Ukraine), technical decisions on the establishment and operation of a technology for preparation and use of spatial data were substantiated. The foundation of the unified geoinformation environment of the Armed Forces should be service-oriented architecture (SOA) of distributed geodatabases. The purpose of deploying service-oriented architectures is to provide a single form of information resources management of the Armed Forces. Deploying a service-oriented architecture allows to create a single interface for internal users, who use both internal data stored in the internal (local) database and external data provided by other vendors. This model of data organization in terms of its architectural construction can be represented as an interconnected set of four levels models (the level of meta descriptions of services and authorizations of different categories users; the level of functional web services and access portals;the level of integration with legacy applications, databases and services, the level of technology reengineering and information system development).The geoinformation space of the UACS of the Armed Forces of Ukraine should be formed as an environment (network) of interconnected geoportals, the purpose of that is to consolidate information on available spatial data in the UACS of the Armed Forces of Ukraine environment. It’s determined that it’s optimal to use ESRI's ArcGIS server multi-user software with Enterprise performance level and Advanced functionality class as a software component.

У ході проведення досліджень з метою забезпечення наведених у даній статті загальних вимог до геоінформаційного забезпечення Єдиної автоматизованої системи управління Збройними Силами України (ЄАСУ ЗСУ) були обґрунтовані технічні рішення з питань створення та функціонування єдиної технології підготовки і використання просторових даних. Фундаментом єдиного геоінформаційного середовища ЗСУ повинна бути сервісно-орієнтована архітектура (СОА) розподілених баз геоданих. Метою розгортання сервісно-орієнтовані архітектури є забезпечення єдиної форми управління інформаційними ресурсами ЗСУ. Розгортання сервісно-орієнтованої архітектури дозволяє створити єдиний інтерфейс для внутрішніх користувачів, що використовують як внутрішні дані, які зберігаються у внутрішній (локальній) базі даних, так і зовнішні дані, надані іншими постачальниками. Дана модель організації даних з точки зору її архітектурної побудови може бути представлена у вигляді взаємозв’язаної сукупності моделей чотирьох рівнів (рівень метаописів сервісів і авторизації користувачів різних категорій; рівень функціональних веб-сервісів і порталів доступу; рівень інтеграції з успадкованими додатками, базами даних і сервісами; рівень технологій реінжинірингу і розвитку інформаційної системи).Єдиний геоінформаційний простір ЄАСУ ЗСУ має утворюватися як середовище (мережа) взаємопов’язаних геопорталів, призначення яких полягає в консолідації інформації щодо наявних у ЄАСУ ЗСУ просторових даних, які оформлюються і надаються для використання у вигляді геосервісів, а також створенні єдиної точки входу користувачів у дане середовище. Визначено, що у якості програмної складової оптимально застосовувати серверне програмне багатокористувацьке забезпечення ArcGIS компанії ESRI з рівнем продуктивності Enterprise та класом функціональності Advanced.
ПРИНЦИПИ СТВОРЕННЯ ТА ФУНКЦІОНУВАННЯ ЄДИНОГО ГЕОІНФОРМАЦІЙНОГО СЕРЕДОВИЩА ЗБРОЙНИХ СИЛ УКРАЇНИ
Keywords: geoinformation support; service-oriented architecture (SOA); geospatial data; geoportal; геоінформаційне забезпечення; сервісно-орієнтована архітектура (СОА); геопросторові дані; геопортал